The Effect of Systemic Chemotherapy on Survival in Patients With Localized, Regional, or Metastatic Adenocarcinoma of the Urinary Bladder. (August 2020) - Luzzago, Stefano; Palumbo, Carlotta; Rosiello, Giuseppe; Pecoraro, Angela; Deuker, Marina; Mistretta, Francesco A.; Tian, Zhe; Musi, Gennaro; Montanari, Emanuele; Shariat, Shahrokh F.; Saad, Fred; Briganti, Alberto; et al.
Abstract : Objectives: To test the effect of systemic chemotherapy on cancer-specific mortality (CSM) in patients with adenocarcinoma of the urinary bladder (ADKUB). Materials and Methods: Within the Surveillance, Epidemiology, and End Results registry (2004 to 2016), we identified patients with localized (T2-3N0M0), regional (T4N0M0/TanyN1-3M0), and metastatic (TanyNanyM1) ADKUB. Temporal trends, Kaplan-Meier plots, and multivariable Cox regression models were used before and after 1:1 propensity score matching and inverse probability of treatment weighting. Results: Of 1537 patients with ADKUB, 834 (54.0%), 363 (23.5%), and 340 (22.5%) harbored localized, regional, and metastatic disease, respectively. The rates of chemotherapy use increased in localized (estimated annual percentage change [EAPC]: +2.7%; P =0.03) and regional ADKUB (EAPC: +2.4%; P =0.04). Conversely, chemotherapy rates remained stable in metastatic patients (EAPC: +1.6%; P =0.4). In multivariable Cox regression models, chemotherapy use was associated with lower CSM in metastatic ADKUB (hazard ratio [HR]: 0.5; P =0.003), but not in either localized (HR: 0.8; P =0.2) or in regional ADKUB (HR: 1.0; P =0.9). In metastatic ADKUB, the benefit of chemotherapy on CSM persisted after 1:1 propensity score matching (HR: 0.6; P =0.002) and after inverse probability of treatment weighting (HR: 0.4; P <0.001). Conclusions: Chemotherapy improves survival in metastatic ADKUB. However, only one out of 2 such patients benefit from chemotherapy. In consequence, greater emphasis on chemotherapy use may be warranted in these patients. Conversely, no benefit was identified in localized or regional ADKUB. Abstract : Supplemental Digital Content is available in the text.